Aristocratic amateurs to fat cats? British CEOs in the twentieth century - Robin J. C. Adams; Michael Aldous; Philip Fliers; John D. Turner (Queen's University Centre for Economic History (QUCEH), 2023)
This article uses a prosopographical methodology and a new dataset of 1,558 CEOs from Britain's largest public companies between 1900 and 2009 to analyse how the role, social background, and career pathways of corporate leaders changed. We have four main findings: First, the designation of CEO only prevailed in the 1990s. Second, the proportion of socially elite CEOs was highest before 1940, but they were not dominant. Third, most CEOs did not have a degree before the 1980s, or professional qualification until the 1990s. Fourth, liberal market reforms in the 1980s increased the likelihood of dismissal by a factor of three.
Keywords: G30; M12; N83; N84; 330; corporate leaders; corporate careers; Britain; 20th century